Ex Situ Repair of Pre-Hilar Aneurysmal Lesion of the Renal Artery - Fatma Aouini; Abir El Mahdi; Nazih Chaouch; Soumaya Mechergui; Achraf Saaidi; Nabil Ben Romdhane; Jamel Manaa (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2016)
Introduction Renal artery aneurysms (RAAs) are rare. They are often identied incidentally during abdominal computed tomography (CT) screening for other diseases. They are occasionally identied as a rare abdominal emergency due to rupture of a left renal artery aneurysm. In recent years, endovascular therapy such as coil embolization or stentgraft with the coil embolization was successful for treating RAAs, but complex AAs may require aneurysmectomy and renal artery reconstruction by in-situ repair or ex-vivo. Observation We report the case of a 54-year-old-man with a history of hypertension and smoking, followed in urology for lower back pain. Renal ultrasound suspected the presence of a pre-hilar aneurysm, confirmed by CT angiography (Figure 1A) which showed a large and distal aneurysm, extended to the division of arterial branches. The complexity of the lesion has justified the use of ex-situ repair (Figure 1B,C ).